Advances in hexagon mesh-based flow direction modeling. (February 2022) - Liao, Chang; Zhou, Tian; Xu, Donghui; Barnes, Richard; Bisht, Gautam; Li, Hong-Yi; Tan, Zeli; Tesfa, Teklu; Duan, Zhuoran; Engwirda, Darren; Leung, L. Ruby
Abstract: Watershed delineation and flow direction representation are the foundations of streamflow routing in spatially distributed hydrologic modeling. A recent study showed that hexagon-based watershed discretization has several advantages compared to the traditional Cartesian (latitude–longitude) discretization, such as uniform connectivity and compatibility with other Earth system model components based on unstructured mesh systems (e.g., oceanic models). Despite these advantages, hexagon-based discretization has not been widely adopted by the current generation of hydrologic models. One major reason is that there is no existing model that can delineate hexagon-based watersheds while maintaining accurate representations of flow direction across various spatial resolutions. In this study, we explored approaches such as spatial resampling and hybrid breaching-filling stream burning techniques to improve watershed delineation and flow direction representation using a newly developed hexagonal mesh watershed delineation model (HexWatershed). We applied these improvements to the Columbia River basin and performed 16 simulations with different configurations. The results show that (1) spatial resampling modulates flow direction around headwaters and provides an opportunity to extract subgrid information; and (2) stream burning corrects the flow directions in mountainous areas with complex terrain features. Highlights: Hexagon mesh-based flow direction can be coupled with other Earth system components. Resampling mainly affects flow direction near headwaters instead of stream channels. Stream burning improves the river network, especially at coarse resolutions. The hybrid method minimizes its modification to elevations and improves slopes.